1980
DOI: 10.1002/vnl.730020205
|View full text |Cite
|
Sign up to set email alerts
|

Heat stabilizers for poly (vinyl chloride). I. Synergistic systems based on calcium/zinc stearate

Abstract: Synergism in poly(vinyl chloride) stabilization was studied by the determination of the dynamic and static stability of 34 different formulations. Nine ratios of Ca/Zn stearate were tested. Both the static and the dynamic stability increased almost linearly with the calcium stearate content, but unfortunately the initial discoloration increased as well. Melt viscosity decreased with an increasing content of calcium stearate. This was mainly caused by the difference in lubrication effect between calcium stearat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…In these heavy metal-stabilised PVC formulations, however, the polyol additive still appears to exert a detrimental effect on the initial colour [5,7]. Since natural polyols may significantly contribute to the development of environmentally benign (next generation) stabiliser systems, we have investigated their effect on the initial colour of a heavy metal-and zinc-free PVC formulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these heavy metal-stabilised PVC formulations, however, the polyol additive still appears to exert a detrimental effect on the initial colour [5,7]. Since natural polyols may significantly contribute to the development of environmentally benign (next generation) stabiliser systems, we have investigated their effect on the initial colour of a heavy metal-and zinc-free PVC formulation.…”
Section: Discussionmentioning
confidence: 99%
“…To inhibit discolouration during long-term heat exposure (natural) polyols are already applied as secondary heat stabilisers in heavy metal-stabilised PVC compounds [1e7]. Unfortunately, however, in these PVC formulations the polyol additives exert a detrimental effect on the initial colour [5,7]. We recently reported that for heavy metal-and zinc-free PVC formulations (natural) polyols, especially those containing primary hydroxyl groups, act as HCl scavengers by substitution of the primary hydroxyl moieties by chloride ions [8].…”
Section: Introductionmentioning
confidence: 99%
“…The epoxy group of the plasticizer is excellent hydrochloric acid scavenger; hydrochloric acid absorption occurs readily. [18][19][20] The formation of polyene sequences was investigated by UV-visible spectroscopy. The influence of the weight of the epoxidized oil and the amount of oxirane oxygen in the ESO were considered.…”
Section: Evolution Of Discolorationmentioning
confidence: 99%
“…[22] b) Modification of molecular weight distribution, which is produced by the chain scission reactions [3,5,11] (which produce a decrement in E and s, and an increment of e [23]) and the chain branching reactions (which produce the opposite effect [23] ) occurring simultaneously during the heating process. c) Decrease of the magnitude of intermolecular interactions, due to a decrement in the global polarity of the system, which occurred as a consequence of the elimination of many C-Cl polar bonds; this produces a softening of the material.…”
Section: Dehp Effect On Nph Formulationsmentioning
confidence: 99%
“…[8,[10][11][12] Besides, Thomas [12] suggested that ZnCl 2 formation is prevented, when enough calcium stearate (CaSt 2 ) is present in the system. It has also been reported that mixtures of CaSt 2 and ZnSt 2 are able to form a complex through heating.…”
Section: Introductionmentioning
confidence: 99%